Single-cell manipulation by two-dimensional micropatterning - Xuehe Ma; Haimei Zhang; Shiyu Deng; Qiushuo Sun; Qingsong Hu; Yuhang Pan; Fen Hu; Imshik Lee; Fulin Xing; Leiting Pan (Journal of Innovative Optical Health Sciences, 2024)
Cells are highly sensitive to their geometrical and mechanical microenvironment that directly regulate cell shape, cytoskeleton and organelle, as well as the nucleus morphology and genetic expression. The emerging two-dimensional micropatterning techniques offer powerful tools to construct controllable and well-organized microenvironment for single-cell level investigations with qualitative analysis, cellular standardization, and in vivo environment mimicking. Here, we provide an overview of the basic principle and characteristics of the two most widely-used micropatterning techniques, including photolithographic micropatterning and soft lithography micropatterning. Moreover, we summarize the application of micropatterning technique in controlling cytoskeleton, cell migration, nucleus and gene expression, as well as intercellular communication.